IMPROVING THE STUDENTS’ SPEAKING ABILITY THROUGH MINI-VIVA ASSESSMENT STRATEGY - Muhammad Arief Paturusi (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2014)
Speaking or oral communication is a process between speaking and writing are productive skill, reading and listening are the receptive skill of understanding. The speaker has to encode the message that he wants? to convey an appropriate language. The objectives of the study are to find out the improvement of the students’ accuracy and fluency in speaking through the use of Mini-Viva Assessment Strategy. This research used a Pre-experimental Design with one group pre-test and post-test score that depended on the success of the treatment, it aimed to explain the effectiveness of Mini- Viva Assessment Strategy to improve speaking skill. Using Mini- Viva Assessment Strategy in teaching speaking is able to improve the students’ accuracy which deals with pronunciation, grammar, and vocabulary at the Eleventh Grade of SMA Negeri 1 BajengGowa. The students’ accuracy deals with pronunciation. It is proven by the improvement of the students’ pronunciation is 31.89%; the students’ accuracy deals with grammar.It is proven by the improvement of the students grammar is 56.80%, and the students’ accuracy deals with vocabulary. It is proven by the improvement of the students' vocabulary is 52.11%. Using Mini- Viva Assessment Strategy in teaching speaking is able to improve the students’ fluency which deals with self-confidence and smoothness at the Eleventh Grade of SMA Negeri 1 Bajeng Gowa. The students’ fluency deals with self-confidence. It is proven by the improvement of the students’ self-confidence is 37.85%. The students’ fluency deals with smoothness. It is proven by the improvement of the students’ smoothness is 34.37%. Using Mini- Viva Assessment Strategy in teaching speaking is able to improve the students’ speaking ability which deals with accuracy and fluency at the Eleventh Grade of SMA Negeri 1 BajengGowa.The improvement of the students’accuracy is 46.15% and the improvement of the students’ fluency is 36.23%. Mini- Viva Assessment strategy is significant to improve the students’ speaking ability.Keywords: speaking, strategy, Mini-Viva Assessment,